2015
DOI: 10.1246/cl.150119
|View full text |Cite
|
Sign up to set email alerts
|

Tellurophenes and Their Emergence as Building Blocks for Polymeric and Light-emitting Materials

Abstract: He has published over 70 articles thus far in the domain of molecular main group element and polymer chemistry with specific interests in inorganic hydrides and the use of metallacycle transfer to create new optoelectronic materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…163,164 More recently the Seferos group has published a comprehensive review on polytellurophenes for high performance applications, 165 while Rivard also described the use of tellurophenes as light-emitting materials in a separate review article. 166 As a result, we will review tellurium containing π-conjugated materials with optoelectronic applications that have emerged since these most recent reviews were published. Building upon their initial work containing dibromo-and dichloro-adducts of tellurophenes, 167 the Seferos group reported the photoreductive elimination of bromine, chlorine and quite impressively, fluorine, from 2,5diphenyldihalotellurophenes.…”
Section: Telluriummentioning
confidence: 99%
“…163,164 More recently the Seferos group has published a comprehensive review on polytellurophenes for high performance applications, 165 while Rivard also described the use of tellurophenes as light-emitting materials in a separate review article. 166 As a result, we will review tellurium containing π-conjugated materials with optoelectronic applications that have emerged since these most recent reviews were published. Building upon their initial work containing dibromo-and dichloro-adducts of tellurophenes, 167 the Seferos group reported the photoreductive elimination of bromine, chlorine and quite impressively, fluorine, from 2,5diphenyldihalotellurophenes.…”
Section: Telluriummentioning
confidence: 99%
“…Reports of tellurophene containing polymers are considerably less numerous than selenophene containing materials, probably in part due to the synthetic challenges of tellurophene chemistry. 10 , 11 In addition many of the examples reported to date are co-polymers, with relatively low loadings of tellurophene in which there is a potential that the intrinsic influence of the heteroatom is masked. 12 20 Homo-polymers of tellurophene are rare, with the first substituted tellurophene polymer, poly(3,4-dimethoxytellurophene), 21 prepared as an insoluble film by electrochemical polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic tellurium heterocyclestellurophenesare more synthetically accessible, and their photophysical properties have been studied by the Rivard group. 58 It was found that tellurophenes can achieve room temperature phosphorescence when substituted with boronates (14). 59 Some tellurophene derivatives displayed aggregation-induced emission, 60 which also has potential use in materials applications.…”
Section: Future Directionsmentioning
confidence: 99%